Making FAT10 with a Reactive C-terminus for E3 Ligase Screening - Cao, Jinjing; Schmidtke, Gunter (Archives of Clinical and Biomedical Research, 2025)
Background: FAT10, a ubiquitin-like modifier, targets proteins to the 26S proteasome for degradation, similar and in addition to ubiquitin. However, FAT10 utilizes its own enzyme cascade, including E1 (UBA6), E2 (USE1), and various E3 ligases. To date, Parkin is the only identified E3 ligase for FAT10, but about 800 different E3-enzymes were reported for ubiquitin. In this study, we aimed to generate a branched FAT10-USE1 conjugate with a reactive C-terminus for the purpose of screening potential E3 ligases. Our method is simple, cost effective and does not require expensive lab equipment. We were able to avoid organic solvents and extreme pH or salt conditions. Methods: The proteins were expressed at a low temperature for 7–8 hours and purified using affinity resin. Conjugation was achieved through a radical thiol–yne coupling reaction. The resulting products were analyzed by Coomassie Brilliant Blue staining and Western blotting. Results: FAT10-SH was successfully purified using a Strep-Tactin column and chitin resin, while USE1-GFP was purified via Ni-affinity chromatography. Notably, FAT10-alkene-USE1-GFP conjugates were successfully generated using IA-alkyne, but not STP-alkyne. Conclusion: In this study, we developed novel FAT10-based probes suitable for E3 ligase screening, which may facilitate future investigations into FAT10 biology. The method can be easily adapted to other ubiquitin like modifiers.